MENGUNYAH BUAH APEL ROYAL GALA TERHADAP PEMBENTUKAN PLAK DAN DERAJAT KEASAMAN SALIVA PADA SISWA KELAS VI SDIT ASSUNNAH KOTA CIREBON: CHEWING ROYAL GALA APPLES ON THE FORMATION OF PLAQUE AND pH SALIVA IN GRADE VI STUDENTS OF SDIT ASSUNNAH CIREBON - Aprillia Dini Sulistyanti; Emma Kamelia; Hadiyat Miko; Tritania Ambarwati; Rena Setiana (JDHT Journal of Dental Hygiene and Therapy, 2021)
Plaque and pH saliva are factors that can cause dental caries. The prevalence of caries according to RISKESDAS (2018) reached 45.3% in Indonesia. WHO (2012) states that the prevalence of caries for school children at 60%-90%. They are fond of consuming cariogenic foods that can increase the risk of caries. The Royal Gala Apple contains antibacterial that can inhibit plaque formation and have a slight acid flavor that can stimulate saliva flow. Aim: To know the influence of chewing the Royal Gala Apples to plaque formation and pH saliva in grade VI students SDIT Assunnah Cirebon. Method: Quasi experiment with one group pretests posttest design. Samples of 33 students. The samples were instructed to chew the Royal Gala Apple 100 gr for 5 minutes. Plaque measured by PHP index and pH saliva is measured with universal indicator paper. Results: The normality test of Kolmogorov-Smirnov is obtained by the plaque and pH saliva results before and after chewing the royal Gala p-value of < 0.05 so, that distribution data is abnormal. Data analyzed using Wilcoxon test was obtained PHP plaque index and pH saliva before and after chewing Apple Royal Gala p-value: 0.000 (sig < 0.05) Conclusion: there is a chewing effect of the Royal Gala Apple Fruit against plaque formation and pH saliva in grade VI students SDIT Assunnah Cirebon.